2021
DOI: 10.3390/ijms222011007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mutation of β-Spectrin in Hereditary Spherocytosis Using Whole Exome Sequencing

Abstract: Hereditary spherocytosis (HS), the most commonly inherited hemolytic anemia in northern Europeans, comprises a group of diseases whose heterogeneous genetic basis results in a variable clinical presentation. High-throughput genome sequencing methods have made a leading contribution to the recent progress in research on and diagnostics of inherited diseases and inspired us to apply whole exome sequencing (WES) to identify potential mutations in HS. The data presented here reveal a novel mutation probably respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This study indicated that the most frequently affected genes in Turkish children with HS were ANK1and SPTB. This result is similar to previous results found in American, European and Chinese populations (19)(20)(21). All mutations are novel and unique, having not previously been reported in a different population.…”
Section: Discussionsupporting
confidence: 92%
“…This study indicated that the most frequently affected genes in Turkish children with HS were ANK1and SPTB. This result is similar to previous results found in American, European and Chinese populations (19)(20)(21). All mutations are novel and unique, having not previously been reported in a different population.…”
Section: Discussionsupporting
confidence: 92%
“…Pathological lesions in HS result mainly from the loss of spectrin and/or ankyrin that is normally responsible for anchoring the membrane skeleton in the lipid bilayer. The current knowledge is constantly updated with new mutations resulting in the HS phenotype [10,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Many interactions between membrane skeleton proteins and also membrane skeleton proteins with membrane bilayer containing integral membrane proteins via proteins and lipids were discovered due to identification of naturaly occuring mutants which are mostly related to haemolytic anaemias [1][2][3]. These mutants have become the subject of many studies to elucidate the regulatory mechanisms of spectrin-ankyrin interaction, which has significantly increased our knowledge of the structure and function of the erythrocyte membrane skeleton [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During our studies on HS cases in the Polish population [ 29 31 ], we identified erythrocyte membrane protein abnormalities in the studied family in which two members (brothers, RK and MK) displayed symptoms of hemolytic anemia that did not fit the characteristics of the known disease [ 32 ]. We used high-throughput sequencing technologies and functional studies to characterize the molecular basis of this anemia case.…”
Section: Introductionmentioning
confidence: 99%